Teori Overcriminalization dalam Kriminalisasi Perbuatan di Era Digital - ANDIKA KURNIAWAN (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The Development Of Digital Technology Has Led To The Expansion Of Criminalization Through Law Number 1 Of 2024 Concerning The Second Amendment To Law Number 11 Of 2008 Concerning Electronic Information And Transactions (ITE Law). This Study Aims To Analyze The Potential For Overcriminalization In The Regulation Of Cybercrime Based On The Principle Of Ultimum Remedium. The Method Used Is Normative Legal Research With A Statutory And Conceptual Approach. The Results Indicate That Several Criminal Provisions In The ITE Law Have The Potential To Lead To Overcriminalization If Applied Broadly Without Clear Boundaries. Therefore, Law Enforcement Guidelines Are Needed That Prioritize A Non-Criminal Approach And Emphasize The Criteria For Proportional Criminalization.